Prognostic and diagnostic value of [18F]FDG-PET/CT in restaging patients with small cell lung carcinoma: an Italian multicenter study. Issue 8 (August 2019) - Quartuccio, Natale; Evangelista, Laura; Alongi, Pierpaolo; Caobelli, Federico; Altini, Corinna; Cistaro, Angelina; Lambertini, Alessandro; Schiorlin, Ilaria; Popescu, Cristina E.; Linguanti, Flavia; Laudicella, Riccardo; Scalorbi, Federica; et al.
Abstract : Background: The presence of residual disease after initial treatment in small cell lung cancer (SCLC) influences prognosis and impacts patient management. To date, few data exist on the value of fluorine-18-fluorodeoxyglucose ([ 18 F]FDG)-PET/computed tomography (CT) in SCLC at restaging. Therefore, in restaging patients with SCLC, we aimed to (a) evaluate the prognostic value yielded by [ 18 F]FDG-PET/CT and (b) assess the diagnostic agreement between [ 18 F]FDG-PET/CT and contrast-enhanced computed tomography (ceCT). Patients and methods: From a multicenter database, we evaluated 164 patients with SCLC who underwent [ 18 F]FDG-PET/CT for restaging purposes. PET scans were evaluated visually to identify the presence of recurrence. For each patient, the maximum and the mean standardized uptake value (SUVmax and SUVmean, respectively), metabolic tumor volume, and total lesion glycolysis were calculated, taking into account the lesion with the highest [ 18 F]FDG uptake (namely, the index lesion) in the local recurrences, lymph node involvement, and distant metastasis categories. Kaplan–Meier curves were computed to assess the effects of [ 18 F]FDG-PET/CT findings on overall survival (OS) and progression-free survival. Furthermore, the agreement between PET/CT and ceCT in detecting metastases was evaluated in 119 patients on a patient-based analysis (Cohen's κ ; P < 0.05). Results: The presence of metastatic lesions at [ 18 F]FDG-PET/CT was associated with a significantly shorter OS ( P = 0.039) and progression-free survival ( P < 0.001). Higher SUVmax showed a trend toward a shorter OS ( P = 0.065). The K-agreement between ceCT and PET/CT in recurrent SCLC was 0.37 ( P < 0.001). PET/CT and ceCT showed the same number of lesions in 52 (43.7%) patients, whereas PET/CT detected additional lesions in 35 (29.4%) patients. Conclusion: Detection of metastatic lesions at restaging by [ 18 F]FDG-PET/CT can predict a higher rate of progression and negatively influence OS in patients with SCLC. [ 18 F]FDG-PET/CT and ceCT seem to be complementary imaging modalities in patients with metastatic SCLC.